2018
DOI: 10.1038/s41590-018-0180-5
|View full text |Cite
|
Sign up to set email alerts
|

IgG3 regulates tissue-like memory B cells in HIV-infected individuals

Abstract: Immunoglobulin G3 (IgG3) has an uncertain role in the response to infection with and vaccination against human immunodeficiency virus (HIV). Here we describe a regulatory role for IgG3 in dampening the immune system-activating effects of chronic HIV viremia on B cells. Secreted IgG3 was bound to IgM-expressing B cells in vivo in HIV-infected chronically viremic individuals but not in early-viremic or aviremic individuals. Tissue-like memory (TLM) B cells, a population expanded by persistent HIV viremia, bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 53 publications
(57 reference statements)
1
31
0
Order By: Relevance
“…As a result, TLM B cells are more adversely affected functionally than naïve B cells. Consistent with the highly clustered IgM-BCR observed by high-resolution microscopy in our studies and reported in other conditions of chronic signaling (39), basal levels of phosphorylated signaling intermediates are increased on IgG3-bound TLM B cells (38). However, these affected B cells also respond poorly to stimulation through the IgM-BCR, as measured by induced phosphorylation of downstream intermediates and intracellular calcium mobilization, and this unresponsiveness is most pronounced on IgG3-bound TLM B cells whereas the binding of IgG3 to naïve B cells does not alter their capacity to signal.…”
Section: Binding Of Igg3 To B Cells Of Hiv-1-infected Individualssupporting
confidence: 92%
See 2 more Smart Citations
“…As a result, TLM B cells are more adversely affected functionally than naïve B cells. Consistent with the highly clustered IgM-BCR observed by high-resolution microscopy in our studies and reported in other conditions of chronic signaling (39), basal levels of phosphorylated signaling intermediates are increased on IgG3-bound TLM B cells (38). However, these affected B cells also respond poorly to stimulation through the IgM-BCR, as measured by induced phosphorylation of downstream intermediates and intracellular calcium mobilization, and this unresponsiveness is most pronounced on IgG3-bound TLM B cells whereas the binding of IgG3 to naïve B cells does not alter their capacity to signal.…”
Section: Binding Of Igg3 To B Cells Of Hiv-1-infected Individualssupporting
confidence: 92%
“…Given the effects of T-bet on immunoglobulin class-switching and our observations of a strong association between T-bet expression and TLM B cells in HIV-1-infected individuals (Figure 1), we began to survey our large and diverse cohort of HIV-1-infected individuals to delineate how IgG subclass expression was associated with HIV-1 disease status. Unexpectedly, we discovered a novel and unique mechanism of B-cell regulation in HIV-1 infection mediated by the binding of soluble IgG3 to IgM-BCR expressing B cells (38). This does not negate an IgG3-skewing effect of T-bet expression, to the contrary, the individuals identified with IgG3-bound B cells (referred to as affected individuals or B cells) also had higher serum concentrations of IgG3 and greater ratios of IgG3 to IgG2 compared to those who did not have affected B cells, indicating that IgG3-expressing and -secreting B cells were being selectively induced.…”
Section: Binding Of Igg3 To B Cells Of Hiv-1-infected Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies provided evidence for a novel mechanism by which TLMBCs are regulated in HIV-infected chronically viremic individuals. 26 Secreted IgG3 was observed selectively bound to TLMBC by a mechanism involving FcγRIIb, the complement component, C1q and C reactive protein. The concentration of IgG3 in serum positively correlated with the amount of IgG3 bound to TLMBCs.…”
Section: The D Iscovery Of At Ypi C Al Mbc Smentioning
confidence: 97%
“…The function of tissue-based B cells in mucosal associated lymphoid tissues is not known. 26 22 Because the patterns of inhibitory receptors and chemokine receptors for homing to sites of inflammation expressed by TLMBC were similar to those of exhausted T cells the term "exhausted MBCs" was also applied.…”
Section: Introductionmentioning
confidence: 99%